Evaluation of Students' Engagement in Integrated Learning Model in A Blended Environment - Tatiana Baranova; Liudmila Khalyapina; Aleksandra Kobicheva; Elena Tokareva (MDPI AG, 2019)
As new informational conditions contribute to the discovery of new ways to improve the quality of the educational process, a new integrated learning model was elaborated. The purpose of the paper is to evaluate the students’ engagement in a newly-introduced integrated learning model, identify the impact of such a model on students’ learning outcomes, and to determine if students’ engagement levels influence their learning outcomes. For our research we used qualitative and quantitative data of students’ records of professional discipline and English testing, surveys and interviews on behavioral engagement, emotional engagement, and cognitive engagement (N = 63). Results on students’ engagement showed that online activity, especially the online international project, involved students more than face-to-face classes, but at the same time some of them noted that without lectures it would be difficult, or even impossible, to participate in a project. Thus the overall engagement level was quite high. Additionally, an integrated approach positively impacted learners’ outcomes. The correlation analysis showed that learners’ engagement played an influential role and highly impacted students’ learning results. In this case we can conclude that our integrated learning model contributes to students’ involvement in the educational process and, as a consequence, allows them to achieve greater results.